Quantitative analysis of castration resistant prostate cancer progression through phosphoproteome signaling. - Lescarbeau, Reynald M.; Kaplan, David L. (2016)
Background: Although recent progress has been made in treating castration resistant prostate cancer, the interplay of signaling pathways which enable castration resistant growth is incompletely understood. A data driven, multivariate approach, was used in this study to predict prostate cancer cell survival based on the phosphorylation levels of key proteins in PC3, LNCaP, and MDA-PCa-2b cell lines in response to EGF, IGF1, IL6, TNFα, dihydrotestosterone, and docetaxel treatment.; Keywords: Prostate cancer, Phosphoproteome, Castration resistance, Regression analysis, Cell signaling.; Springer Open.